A MIXED-METHODS CROSS-SECTIONAL STUDY ASSESSING THE IMPACT OF LANGUAGE DIFFICULTIES ON KNOWLEDGE ACQUISITION AND ACADEMIC SUCCESS AMONG FIRST-YEAR NATURE CONSERVATION STUDENTS AT MANGOSUTHU UNIVERSITY OF TECHNOLOGY. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Language proficiency is a critical factor in higher education success, especially in disciplines like Nature Conservation that demand strong conceptual understanding and technical vocabulary. At Mangosuthu University of Technology (MUT), many first-year students from multilingual backgrounds face language barriers that may hinder their learning and academic performance. This study examines the impact of language difficulties on knowledge acquisition and academic success among first-year Nature Conservation students. Methods A cross-sectional mixed-methods study design was employed. Quantitative data were collected through standardized English language proficiency assessments and academic performance records of 120 first-year Nature Conservation students enrolled in 2025. Qualitative data were gathered through focus group discussions (n=4) and semi-structured interviews (n=15), which explored students’ experiences with language challenges in lectures, assessments, and practical sessions. Statistical analysis included correlation testing between language proficiency and academic performance, while qualitative data were analyzed thematically. Results The sample consisted of 120 students (53% female, 47% male; mean age = 19.4 years). Quantitative results showed a moderate positive correlation (r = 0.58, p < 0.01) between English proficiency and academic performance, with students scoring higher in theoretical modules demonstrating better language skills. Qualitative findings indicated that language barriers led to reduced classroom engagement, misinterpretation of key concepts, and difficulty in academic writing. Students reported challenges with translating ecological terms and field-specific vocabulary, leading to reduced confidence. Coping strategies included forming peer study groups, using bilingual resources, and dedicating extra time to self-study. Conclusion Language barriers significantly hinder first-year Nature Conservation students’ ability to acquire and apply knowledge. These challenges impact their academic performance and contribute to educational inequality. Recommendations Institutions should implement academic language support tailored to the Nature Conservation curriculum, provide bilingual resources, and train lecturers in linguistically responsive teaching strategies to improve academic outcomes and promote equity.